Comparison of DNA fingerprint patterns of isolates of Mycobacterium africanum from east and west Africa - Haas, Walter; Bretzel, Gisela; Amthor, Beate; Schilke, Kathrin; Krommes, Gero; Rüsch-Gerdes, Sabine; Sticht-Groh, Veronica; Bremer, Hans J. (Journal of clinical microbiology, 1997)
Mycobacterium africanum is a pathogen found in tuberculosis patients in certain parts of Africa and is a member of the Mycobacterium tuberculosis complex. Biochemically, strains of M. africanum exhibit a high degree of variability, with some tendency to cluster according to their geographical origin. To investigate whether this phenotypic variability is reflected at the genetic level, we performed DNA fingerprint analysis of strains isolated from patients with pulmonary tuberculosis in Uganda and Sierra Leone. IS6110 DNA fingerprinting was carried out by the mixed-linker PCR method. A total of 138 strains of M. africanum were analyzed: 42 isolates from Uganda and 96 isolates from Sierra Leone. With few exceptions, the resulting DNA fingerprint patterns grouped together according to their country of origin. A striking lack of variability of DNA fingerprints was found for strains from Sierra Leone, where 70 of 96 isolates (61.5%) fell into clusters. The two largest clusters accounted for 41.7% of all isolates and differed by only one band, as confirmed by standard DNA fingerprinting. In contrast, only two clusters (7.1%) with two and three isolates, respectively, were found for M. africanum isolates collected in Uganda, and three of the DNA fingerprints contained fewer than seven bands. Strains of M. tuberculosis collected and processed during the same time period were highly variable in both countries. Our results support the concept of geographically defined subtypes of M. africanum. In addition, they demonstrate that natural geographic differences in the variability of IS6110 DNA fingerprints within the M. tuberculosis complex must be considered if this technique is used for epidemiologic studies.